Pengaruh Jarak Tanam dan Jumlah Benih per Lubang Tanam terhadap Pertumbuhan dan Hasil Bawang Merah Asal Biji di Sumatera Barat - Atman Atman; Irfan Suliansyah; Aswaldi Anwar; Syafrimen Yasin (Program Studi Agroteknologi Fakultas Pertanian Universitas Andalas, 2022)
The application of true shallot seed cultivation technology with the planting spacing and number of seedlings per planting hole is expected to increase the productivity of shallots in Indonesia. The research was carried out at KP Sukarami-AIAT West Sumatra from January to June 2021. The aim of the study was to obtain recommendations for the appropriate planting spacing and number of seedlings per planting hole in increasing the growth and yield of true shallot seed in West Sumatra. The study used a 2-factor factorial design in a randomized block with 3 replications. The first factor is the planting spacing (JT), which consists of 3 types, namely: JT1 (10 cm x 10 cm), JT2 (10 cm x 15 cm), and JT3 (15 cm x 15 cm). The second factor is the number of seedlings per planting hole (JB) which consists of 5 types, namely: JB1 (1 seedling), JB2 (2 seedlings), JB3 (3 seedlings), and JB4 (4 seedlings). The results showed that there was not significant interaction between the planting spacing and the number of seedlings per planting hole on the yields of true shallot seed. The highly significant interaction was only found in the growth components and yield components. The best planting spacing is 10 cm x 10 cm and 10 cm x 15 cm, while the best number of seedlings is 1-2 seedlings per planting hole. It is recommended to use a planting spacing of 10 cm x 10 cm or 10 cm x 15 cm with 1-2 seedlings per planting hole in true shallot seed in the highlands of West Sumatra.